Stereoselective Production of Imino‐d‐ribitol and C‐Azanucleosides through Electrochemical C−H Functionalization - Morizumi, Haruka; Okamoto, Kazuhiro; Akahane, Shinnosuke; Takemae, Hitoshi; Oba, Mami; Okada, Yohei; Kitano, Yoshikazu; Mizutani, Tetsuya; Chiba, Kazuhiro (European journal of organic chemistry, 2023)
Herein, we report a practical method for de novo preparation of imino‐d‐ribitol and C‐azanucleosides. The diastereopure Imino‐d‐ribitol was synthesized on a multigram scale by simple manipulation, and late‐stage anomeric derivatization by regio‐ and diastereoselective electrochemical C(sp3)−H activation enabled the efficient synthesis of the corresponding C‐azanucleosides with high β‐selectivity. Completely stereoselective synthesis of C‐azanucleosides was achieved. Assistance of the sterically hindered pentylidene acetal worked well under electrochemical conditions, and redox‐induced N‐α hydroxylation and continuous C‐glycosidation gave desired C‐azanucleosides with high β‐selectivity (>98 %).